2012
DOI: 10.1111/j.1476-4431.2012.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Updates in theAmericanHeartAssociation guidelines for cardiopulmonary resuscitation and potential applications to veterinary patients

Abstract: The prognosis for any patient undergoing cardiopulmonary arrest remains guarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 94 publications
(296 reference statements)
0
13
0
1
Order By: Relevance
“…This issue of the Journal of Veterinary Emergency and Critical Care features a review by Maton and Smarick of the updates made to the 2010 American Heart Association (AHA) CPR guidelines and the relevance of those guidelines to veterinary CPR. 1 The authors succeed in highlighting the most relevant changes in the AHA CPR guidelines. Probably as important, the review also provides a great introductory 'hook' that eloquently and concisely describes the potential pitfalls of applying human CPR guidelines to dogs and cats.…”
Section: Prelude To Recover: Time Is Up For Veterinary Cpr Guidelinesmentioning
confidence: 98%
See 1 more Smart Citation
“…This issue of the Journal of Veterinary Emergency and Critical Care features a review by Maton and Smarick of the updates made to the 2010 American Heart Association (AHA) CPR guidelines and the relevance of those guidelines to veterinary CPR. 1 The authors succeed in highlighting the most relevant changes in the AHA CPR guidelines. Probably as important, the review also provides a great introductory 'hook' that eloquently and concisely describes the potential pitfalls of applying human CPR guidelines to dogs and cats.…”
Section: Prelude To Recover: Time Is Up For Veterinary Cpr Guidelinesmentioning
confidence: 98%
“…This issue of the Journal of Veterinary Emergency and Critical Care features a review by Maton and Smarick of the updates made to the 2010 American Heart Association (AHA) CPR guidelines and the relevance of those guidelines to veterinary CPR . The authors succeed in highlighting the most relevant changes in the AHA CPR guidelines.…”
mentioning
confidence: 99%
“…Mild hypothermia (core body temperature 32 to 34 o C) for 24 to 48 hours postresuscitation has been shown to improve outcome in human clinical trials (Maton and Smarick 2012). Inducing hypothermia (active cooling of the patient using surface-cooling blankets, endovascular-cooling catheters, sedation and neuromuscular blockade) in postarrest human patients is increasingly common and may be beneficial by decreasing tissue oxygen demand and reducing neurological impairment.…”
Section: Postresuscitative Carementioning
confidence: 99%
“…Historically, evidence‐based guidelines for best practice for veterinary cardiopulmonary resuscitation (CPR) for dogs and cats were not available. Suggestions for CPR were extrapolated from human medicine and from expert veterinary opinion with no definitive recommendations . An Internet‐based study showed there to be considerable variation in CPR techniques used across general and referral practices .…”
Section: Introductionmentioning
confidence: 99%
“…Suggestions for CPR were extrapolated from human medicine and from expert veterinary opinion with no definitive recommendations. 1,2 An Internet-based study showed there to be considerable variation in CPR techniques used across general and referral practices. 3 It has been suggested that this disparity in techniques was in part due to a lack of accepted, evidence-based guidelines for…”
Section: Introductionmentioning
confidence: 99%